2022
DOI: 10.1002/ppul.25890
|View full text |Cite
|
Sign up to set email alerts
|

Daytime predictors of nocturnal hypercapnic hypoventilation in children with neuromuscular disorders

Abstract: Objectives To examine objective daytime predictors of nocturnal hypercapnic hypoventilation (NHH) and identify a forced vital capacity (FVC) z‐score cut off that predicts NHH using the 2012 Global Lung Function Initiative (GLI) reference equations in pediatric neuromuscular patients. Design Single‐centre retrospective medical record review. Setting Tertiary pediatric hospital in Australia. Patients Children (<18 years old) with a neuromuscular disorder (NMD) who had a diagnostic sleep study over a 5‐year perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
7
1
Order By: Relevance
“…Whilst the results presented by Frohlich et al 14 In terms of pulmonary function, the results of this study also showed that the expiratory muscle strength (expressed as mean peak expiratory flow) was significantly reduced in the presence of NHH, suggesting an associated higher risk of ineffective cough in these patients.…”
Section: Daytime Predictors Of Nocturnal Hypercapnic Hypoventilation ...contrasting
confidence: 46%
See 3 more Smart Citations
“…Whilst the results presented by Frohlich et al 14 In terms of pulmonary function, the results of this study also showed that the expiratory muscle strength (expressed as mean peak expiratory flow) was significantly reduced in the presence of NHH, suggesting an associated higher risk of ineffective cough in these patients.…”
Section: Daytime Predictors Of Nocturnal Hypercapnic Hypoventilation ...contrasting
confidence: 46%
“…Whilst the results presented by Frohlich et al 14 add relevant information to the clinical management of children with NMD, some aspects of the current study highlight how complicated it is to obtain a straightforward association between pulmonary function decline and NHH.…”
Section: Study Population Design Nhh Definition Daytime Predictor Of ...mentioning
confidence: 79%
See 2 more Smart Citations
“…However, the studies also highlighted some limitations of using the FVC score alone to detect NHH and recommended early screening for NHH even in individuals with FVC > 50%. Frohlich et al 41 found that scoliosis and a decrease in FVC were important predictive factors for NHH. Children with an FVC z‐score <−3.24 had a sensitivity and specificity of 78% and 73%, respectively, for the detection of NHH.…”
Section: Sleep In Neuromuscular Disordersmentioning
confidence: 99%